The development and evaluation of the Patient-Controlled Admission Fidelity Checklist - Maria Smitmanis Lyle; Anna Björkdahl; Clara Hellner; Sigrid Salomonsson; Alexander Rozental (Frontiers in Psychiatry, 2026)
Introduction Patient-Controlled Admission (PCA) is an intervention aimed at increasing patient autonomy by allowing patients to admit themselves to psychiatric inpatient stays without physician assessment or staff gatekeeping. PCA is intended for patients with recurrent need of inpatient care, potentially those who would benefit from increased influence over the admission process. Studies suggest PCA may reduce involuntary care and improve patient empowerment. However, findings are difficult to interpret due to variation in implementation, lack of fidelity assessments, and the absence of an objective fidelity instrument. Aim To develop and evaluate a fidelity measure for PCA capturing core standards of fidelity across clinical settings while remaining acceptable and user-friendly in routine practice. Methods The development process of the fidelity instrument for chart review followed a five-step method: reviewing existing measures, analysing intervention components, drafting a fidelity checklist and guidelines, obtaining expert feedback, and piloting and refinement. Interrater reliability was assessed using Fleiss’ Kappa and percentage agreement, and acceptability and user-friendliness was evaluated in a routine clinical setting using Likert-scale questions. Results The Patient-Controlled Admission Fidelity Checklist (PCA-FC) consists of three parts: A1 (PCA as part of the care plan), A2 (the PCA-agreement), and B (PCA inpatient care). Item-level percentage agreement ranged from 90% to 100%, with several items demonstrating complete agreement. Fleiss’ Kappa coefficients ranged from non-estimable variables for items with no response variability to perfect agreement (κ =1.00). The PCA-FC demonstrated strong acceptability and usability indicating that the checklist was perceived as easy to understand, complete, and apply in practice. Fidelity scores aggregated at the organisational level showed variation, with the lowest adherence observed in inpatient care items. Conclusion The PCA-FC demonstrated high reliability for assessment of PCA fidelity through chart review. It may serve as a useful tool for implementation monitoring, clinical quality assurance, and research on effectiveness of PCA in psychiatric settings. However, fidelity is a multidimensional construct, and the PCA-FC represents an initial step in fidelity assessment that should be complemented by additional methods and further validation.